Effect of SALL4 on the Proliferation, Invasion and Apoptosis of Breast Cancer Cells - Chong Liu PhD; Fan Yao PhD; Xiaoyun Mao PhD; Wanming Li PhD; Hang Chen PhD (Technology in Cancer Research & Treatment, 2020)
Objective: We aimed to identify the expression of Sal-like 4 (SALL4) in breast cancer tissues and to explore the role of this gene in the carcinogenesis of breast cancer cells. Methods: A total of 62 paired breast cancer and noncancerous tissue samples were obtained from patients with breast cancer. SALL4 expression patterns and their association with clinicopathological characteristics were investigated by qRT-PCR, western blotting, and immunochemistry in breast cancer tissues. After the knockdown of SALL4 by short hairpin RNAs (shRNAs), the proliferative, invasive, and apoptotic abilities of MDA-MB-435 and MDA-MB-468 cells (breast cancer cell lines) were measured by colony formation and CCK-8 assays, wound healing and transwell assays, and flow cytometry, respectively. Results: SALL4 expression was higher in breast cancer tissues than that in the paired noncancerous tissues, and increased SALL4 expression in tumor tissues was closely related to tumor size and lymphatic metastasis. Furthermore, functional experiments revealed that SALL4 knockdown inhibited the cell proliferation, induced cell cycle arrest in G0/G1phase and apoptosis, and decreased the ability of migration and invasion in breast cancer cells. Additionally, our study first demonstrated that SALL4 played a critical role in modulating the tumorigenicity of breast cancer cells via the WNT/β-catenin signaling pathway. Conclusions: Our results suggest that the expression of SALL4 is upregulated in breast cancer, and this upregulation is involved in the regulation of cell growth, invasion, and apoptosis. Hence, SALL4 may be a promising target for diagnosis and therapy in patients with breast cancer.